Sketching - Drawing in new methods for Anthropology - Ramos, M. (SKETCHDAY+, 2017)
What is the role of the sketch in the work of architects, artists and designers? An evening of talks, discussion and film screenings, with international invited guest artists and designers who will speak about drawing and sketching in their work. In the era of the digital and the virtual hand held device can we, or should we still draw? And why? Or is there no room in our pockets for the sketchpad alongside the tablet and i-phone? The medium of pen and paper may indeed be just an encumbrance in modern life. In such a routine and utilitarian culture as that of the digital we wonder what is the role of the sketch, of the freehand type of drawing characterised by its immediacy and directness, its expressive intensity and versatility. What are the anthropological and creative consequences for any change in the role of such a vital design and artistic tool as the sketch drawing?